Translational Research. New Findings and Potential Future Applications in Pancreatic Adenocarcinoma - Strimpakos, Alexios S; Syrigos, Kostas N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2012)
The current achievements in pancreatic cancer diagnosis and treatment are disappointing for patients and clinicians alike. Still, in the dawn of 2012, most patients are diagnosed at a late stage where cure is not feasible, with the majority going to succumb within the same year of diagnosis. Thus, the only hope for early and diagnosis and radical treatment is the invention of diagnostic and prognostic tests which might predict accurately patients who may develop this disease and those who have the most aggressive potential, so clinician adopt the appropriate strategy. In this paper we summarize the findings from the three most interesting research abstract as presented at the 2012 American Society of Clinical Oncology Gastrointestinal Cancers Symposium. In particular, we focus on Abstract #160 which shows the diagnostic utility of microRNA serum profiling in pancreatic cancer patients, on Abstract #201 which suggests a potential prognostic role of transforming growth factor (TGF)-beta pathway in advanced pancreatic cancer, and on Abstract #165 which shows that protein S100A4 might be a new, potentially useful, predictive biomarker of gemcitabine efficacy.